A reassessment of sensory evoked potential parameters in multiple sclerosis: a discriminant analysis approach. Issue 2 (February 1981) - Abbruzzese, G; Cocito, L; Ratto, S; Abbruzzese, M; Leandri, M; Favale, E
Abstract : The sensitivity of the different parameters (absolute latency, interwave latency, latency asymmetry, amplitude) of both cervical and cerebral responses evoked by stimulation of the median nerve at the wrist was assessed in patients with multiple sclerosis by discriminant analysis. The peak latency of N13 or N20 SEP components or both was found to be more sensitive than their amplitude, provided that a preliminary covariation with the height of the subjects was performed. The measurement of latency asymmetry between the two sides increased the test's sensitivity, while amplitude asymmetry turned out to be of little diagnostic value. A linear discriminant function with four variates (that is mean amplitude, mean latency, latency asymmetry and height of the subject) was computed to summarise the information provided by the different parameters to give a rapid and exact method for the assessment of SEP abnormalities in multiple sclerosis patients.